Appendiceal collision tumors: case reports, management and literature review - Viel, Giovanni; Ciarleglio, Francesco A.; Frisini, Marco; Marcucci, Stefano; Valcanover, Stefano; Bragantini, Emma; Barbareschi, Mattia; Mereu, Liliana; Tateo, Saverio; Merola, Elettra; Armelao, Franco; De Pretis, Giovanni; et al. (Frontiers in Surgery, 2023)
Appendiceal tumors are incidentally detected in 0.5% cases of appendectomy for acute appendicitis and occur in approximately 1% of all appendectomies. Here, we report two cases of appendiceal collision tumors in two asymptomatic women. In both cases, imaging revealed right-lower-quadrant abdominal masses, which were laparoscopically resected. In both cases, histological examinations revealed an appendiceal collision tumor comprising a low-grade appendiceal mucinous neoplasm and well-differentiated neuroendocrine neoplasm (NEN). For complete oncological control, right hemicolectomy was performed in one patient for the aggressive behavior of NEN; however, histology revealed no metastasis. The other patient only underwent appendectomy. No further treatment was recommended. According to the latest guidelines, exact pathology needs to be defined. Proper management indicated by a multidisciplinary team is fundamental.